ASOSIASI FAKTOR PEMELIHARAAN DAN STATUS INFEKSI NEWCASTLE DISEASE (ND) PADA PETERNAKAN AYAM BURAS DI KECAMATAN TELUK AMBON - Astri Dwiyanti Tagueha (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
The objectives of this study were to determine the status of Newcastle Disease (ND) infection in native chicken at traditional farms, identifying risk factors, and knowing the association between these two. A total of 21 farms were purposively selected from three villages namely Hunuth, Rumah Tiga, and Hative Besar. Positive titre of ND was indicated if Hemaglutination Inhibition (HI) test is â‰¥ 24. The data were analyzed using descriptive statistics and risk ratio (RR) to describe association between variable and positive titre. The results showed from 93 chickensâ€™ blood sample there were 50.5% have ND antibodies. At the farm level, 66.67% of farms are positively infected , i.e : Hunuth 19.05%, Rumah Tiga 19.05%, and Hative Besar 28.57%. Factors that are positively associated with infection status at farm level are respectively : cage usage (1,88), manure treatment (1,46), water source (1,33), treatment of sick chicken (1,64), treatment of new chicken (1,54), treatment of dead chicken (1,64), and fence usage (1,5).